The construction of pad foundation / Muhammad Zulhadzhim Md Sharif - Md Sharif, Muhammad Zulhadzhim (Universiti Teknologi MARA, Perak, 2019)
The starting structure for almost all superstructures is sub-structure. The foundation is a basic and initial structure to support superstructure. The construction of foundation should need to consider a few things before choose the foundations. The element they should consider is the factors contributed to project choose foundations. The examples of the element are the factors contribute projects to use the foundations, the method on site use during works and the problems that will face and solution for the overcome. Arah Semangat Sdn. Bhd. one of the foundations they use pad foundation as their one of foundation on site. The wrong decision of choose the types of foundations use, it will be more problems and troubles will come out to the work of construction at site.